The Relationship of Young Slovak Catholics to the Media - Rončáková, Terézia (Communication Today, 2015)
The article discusses the relationship of young engaged Catholics in Slovakia to the various media outlets which they follow. It attempts to reveal which media outlets are considered to be inspiring and thought-provoking and how are they perceived and evaluated by their followers. The author draws from extensive research into the interpretation of Church news and current affairs within the community of young engaged Catholics; therefore, the findings related to media reception presented herein also include demographical and personality characteristics for individual audiences. The findings are also presented within the context of three specific Church-related news stories: the contentious removal of Róbert Bezák from his position as Archbishop of Trnava, the financial separation of the Church and state, and clerical celibacy. The underlying research was conducted using combined questionnaires, both quantitative and qualitative, on a sample of 339 suitable respondents. The research reveals that the most inspiring Slovak media outlet according to the young engaged Catholics is the secular weekly .týždeň, followed by the Catholic television channel Lux. The research has revealed a significant discrepancy between the opinions of the audiences of secular media and the audiences of official Church media: while the former are very critical of Church media, the latter seem to be more reluctant to turn to secular media.
https://katalog.adlr.link/Record/ai-53-301129